2016
DOI: 10.3382/ps/pev307
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient flow and distribution in conventional cage, enriched colony, and aviary layer houses

Abstract: This study was carried out to measure the mass flow and distribution of nutrients (N, C, S, P, and K) as well as solids and moisture in conventional cage (CC), enriched colony (EC), and aviary (AV) laying-hen houses with Lohmann LSL lite hens located on a commercial laying-hen farm in Iowa. The weight of consumed feed and water, and amounts of eggs and manure production were collected weekly from each house for 2 entire flocks for a total of 28 mo. Samples of feed, egg, manure, litter, and hens were regularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The littered floor of the AV house provided hens access to an average litter area of 520 cm 2 hen -1 for a portion of each day, where deposited manure accumulated throughout the flock cycle. Measurement of manure production and deposition patterns during this study found that 77% to 86% of the manure in the AV was deposited on the manure belt (Lin et al, 2016), with the remainder accumulating on the litter floor. The reduced manure deposition rate within the cage structure of the AV house observed in this study yielded an estimated effective manure-belt SD of 570 to 636 cm 2 hen -1 .…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…The littered floor of the AV house provided hens access to an average litter area of 520 cm 2 hen -1 for a portion of each day, where deposited manure accumulated throughout the flock cycle. Measurement of manure production and deposition patterns during this study found that 77% to 86% of the manure in the AV was deposited on the manure belt (Lin et al, 2016), with the remainder accumulating on the litter floor. The reduced manure deposition rate within the cage structure of the AV house observed in this study yielded an estimated effective manure-belt SD of 570 to 636 cm 2 hen -1 .…”
Section: Methodsmentioning
confidence: 75%
“…Thus, it is possible that, without in-barn drying, manure removal frequency may have a more significant impact on house-level NH 3 emissions, as wetter manure maintained in the house for extended periods has a higher emission potential. Lin et al (2016) performed a nutrient mass balance analysis on the three laying-hen houses monitored in this study, providing periodic measurements of MC and nutrient content (nitrogen, carbon, sulfur, phosphorus, and potassium) of manure at both 3 and 4 d removal intervals. Their study reported that across the two flocks, the average manure MC for EC (46%) was significantly lower than for AV (52%) and CC (54%).…”
Section: Summary Of House-level Average Daily Ammonia (Nh3) Emissiomentioning
confidence: 99%
“…The rate of egg production (or hen-day egg production) was 80% with an average egg weight of 62 g. Cumulative mortality rate was 22% of the initial inventory as of 56 weeks of age. Lin et al (2015) reported mortality rates of 11.6% in aviary, 4.3% in conventional cage and 4.8% in enriched colony houses located in the Midwest. The high mortality rate in the current study might be due to the higher piling probability resulting from the higher number of hens per pen (6000 hen/pen) than that (852-1702 hen/pen) reported by Lin et al (2015).…”
Section: Description Of Monitoring Sitesmentioning
confidence: 99%
“…Lin et al (2015) reported mortality rates of 11.6% in aviary, 4.3% in conventional cage and 4.8% in enriched colony houses located in the Midwest. The high mortality rate in the current study might be due to the higher piling probability resulting from the higher number of hens per pen (6000 hen/pen) than that (852-1702 hen/pen) reported by Lin et al (2015). The house temperature was maintained between 22.2 and 25.6°C.…”
Section: Description Of Monitoring Sitesmentioning
confidence: 99%